Pengembangan buku panduan konseling kelompok kognitif behavioral untuk meningkatkan self management dalam belajar siswa di sekolah menengah kejuruan - Ropesta, Debora; Dharmayanti, Putu Ari; Gading, I Ketut (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
This study aims toi examine the acceptability and effectiveness oif coignitive behavioiral groiup coiunseling toi improive self-management in voicatioinal students' learning. This study uses the 4D develoipment moidel proipoised by Thiagarajan, (1974). This study invoilved 5 guidance coiunseling experts toi assess and test the acceptability oif coignitive behavioiral groiup coiunseling guideboioiks toi improive self-management in voicatioinal students' learning. The assessment instrument used coinsisted oif 22 statement items referring toi the acceptability oif the guideboioik. Validity analysis uses the calculatioin foirmula Cointent Validity Ratioi (CVR) froim Lawshe, (1975). The results shoiw cointent validity (CVI) oif 1 which means very goioid oir special. This shoiws that the develoiped coignitive behavioiral groiup coiunseling guideboioik meets the eligibility criteria. The effectiveness test invoilved 6 students and in the study used the oine groiup pre-test and poist-test design methoid. Test the effectiveness oif coignitive behavioiral groiup coiunseling guideboioiks toi improive self-management in student learning.